Pengembangan Literasi Anak Melalui Metode Pembelajaran Inovatif Dan Aktif Di SDN 3 Bengkaung Batu Layar Lombok Barat - Sawaludin, Sawaludin; Royani, Nispia; Suharni, Suharni (Universitas Negeri Gorontalo, 2023)
Development of children's literacy through learning methods is one of the supporting factors in the implementation of learning carried out in schools. This is a capital for a teacher to create a pleasant and not boring classroom atmosphere, not only that by using good learning methods it greatly affects children's learning outcomes. However, the fact is that teachers at SDN 3 Bengkaung do not understand and pay attention to this. The learning method used is still low order thinking skills. The teaching materials used so far are teaching materials that are oriented towards mastery of concepts in accordance with the material in textbooks that apply nationally. This is what causes the lack of children's learning outcomes, as well as the low literacy skills of children at SDN 3 Bengkaung. That is why the community service activities which are located at SDN 3 Bengkaung, Batu Layar District, West Lombok Regency were carried out by PPKN students at the University of Mataram, by implementing several solutions in the form of innovative and active teaching methods, such as carrying out morning literacy activities, showing educational videos, and coloring the sketch. This is proven to be able to create an active learning atmosphere and restore children's enthusiasm for learning, and provide new knowledge to children.